Effects of repeated yohimbine administration on reinstatement of palatable food seeking: involvement of dopamine D1‐like receptors and food‐associated cues. (29th July 2015) - Ball, Kevin T.; Miller, Leah; Sullivan, Christopher; Wells, Ashleigh; Best, Olivia; Cavanaugh, Brittany; Copus, Taylor; Corrigan, Nathan; Hawkins, Shaina; Kobbe, Krista; Schoener, Ashley; Steiger, Johnathan; et al.
Abstract: Acute exposure to the pharmacological stressor yohimbine induces relapse to both food and drug seeking in a rat model. However, no systematic studies on the effects of chronic stress on relapse have been conducted. Because chronic stress causes changes in dopamine D1 ‐like receptor‐mediated transmission in prefrontal cortex (a relapse node), we tested the hypothesis that chronic exposure to stress increases vulnerability to relapse via dopamine‐mediated mechanisms. Additionally, to determine the role of food‐conditioned cues in reinstatement of food seeking, we made discrete food‐paired cues either available (CS Present) or not available (CS Absent) during extinction and reinstatement testing. Rats responded for palatable food reinforcers in daily 3‐hour sessions, and the behavior was extinguished. To model chronic stress, rats were injected daily with yohimbine (0.0, 2.5, or 5.0 mg/kg; i.p.) during the first 7 days of extinction. Injections were combined with SCH‐23390 (0.0, 5.0, or 10.0 µg/kg; i.p.), a D1 ‐like receptor antagonist. Rats were then tested for reinstatement of food seeking triggered by acute yohimbine (0.0, 1.0, or 2.0 mg/kg; i.p.) and pellet priming. Rats treated previously with chronic yohimbine displayed increased responding following acute yohimbine priming relative to non‐chronically stressed rats, but in the CS Absent condition only. Conversely, the lower dose of chronic yohimbine caused an increase in pellet‐primed reinstatement, but this effect was more pronounced in the CS Present condition. Importantly, SCH‐23390 combined with repeated yohimbine injections attenuated these effects. Thus, chronic stress may increase vulnerability to relapse under specific circumstances via a dopamine D1 ‐like receptor‐mediated mechanism. Abstract : No systematic studies on the effects of chronic stress on relapse to food or drug seeking have been conducted. We report that reinstatement of palatable food seeking by the pharmacological stressor yohimbine and pellet priming were both potentiated in rats with a history of chronic yohimbine exposure relative to non‐chronically stressed rats. Moreover, a dopamine D1‐like receptor antagonist combined with repeated yohimbine injections attenuated this effect. Thus, chronic stress may increase vulnerability to relapse via a D1‐like receptor‐mediated mechanism.